Examining Reliability and Validity of the Jebsen-Taylor Hand Function Test Among Children With Cerebral Palsy. Issue 4 (August 2020) - Tofani, M.; Castelli, E.; Sabbadini, M.; Berardi, A.; Murgia, M.; Servadio, A.; Galeoto, G.
Manual dexterity has strongly predicted functional independence for daily life activities among children with cerebral palsy (CP). The Jebsen-Taylor Hand Function Test (JTHFT) is the most widely used assessment tool for exploring manual dexterity in the CP population, though no research has yet examined its psychometric properties for this use. This cross-sectional study explored the validity and internal consistency of the JTHFT in an Italian sample of inpatient and outpatient children with CP aged between 6-18 years (35 girls and 49 boys). We calculated internal consistency with Cronbach's alpha and tested validity against the Manual Ability Classification System (MACS) using Pearson's correlation coefficient. To better understand how the JTHFT compares with different levels of the MACS, we performed dominant hand timing variability for each test item. Results showed excellent internal consistency with a Cronbach's alpha of .944 and .911, respectively, for nondominant and dominant hands. There was also a statistically significant positive linear Pearson's correlation coefficient between the JTHFT and the MACS ( p  <   .01). We observed high variability in writing performance (Item 1 of the JTHFT) within this sample for each level of the MACS. This study confirms that the JTHFT is a valid assessment tool when used in children with CP aged 6-18 years.